General Aviation Weather Hazards:Current Human Factors Research, Pilot Practices, and Tools. (December 2020) - Blickensderfer, Beth; Brown, Lori J; Greenman, Alyssa; King, Jayde; Pitts, Brandon
When General Aviation (GA) pilots encounter unexpected weather hazards in-flight, the results are typically deadly. It is unsurprising that the National Transportation Safety Board repeatedly lists weather related factors in GA flight operations as an unsolved aviation safety challenge. Solving this problem requires multidisciplinary perspectives. Fortunately, in the past several years innovative laboratory research and industry products have become available. This panel discussion brings together Human Factors and Ergonomics researchers and practitioners to discuss and describe the current work and future directions to avoid weather related accidents in GA.